Between Lines and Beyond Boundaries: Alootook Ipellie’s Entanglements of Space - Desrochers-Turgeon, Émélie (Études Inuit Studies, 2020)
Manifold representations of the dwelling are expressed in the work of artist, poet, writer, editor, and activist Alootook Ipellie in the bi-monthly publication Inuit Today in the 1970s and 1980s, as a cross-section through key moments in Inuit Nunangat history. This essay thus examines Ipellie’s representations of space—not as an attempt to theorize Inuit space but rather to offer reflections on how these representations challenged ways of knowing and interpreting Arctic communities. We first address the Arctic representation in Ipellie’s work, which emphasizes the existing richness of the land according to Inuit perspectives as opposed to Qallunaat (non-Inuit) interpretations. His drawings also offer political comments on land disputes and the exploitation of territory. We then explore the representation of buildings, as Ipellie witnessed the transition from traditional to government housing. Ipellie’s humour-based approach constituted a strong social and political critique of housing issues and settler-colonial building practices. This artist acknowledged Inuit ingenuity when speaking of traditional housing, thus advocating for Inuit knowledge, invention, and built heritage. Lastly, we discuss the representation of multiple voices in the struggles over space, including Inuit communities and non-human agents, such as animals and land. Dwelling on the notion of “lines” and “the in-between”, we consider the thickness of Ipellie’s drawn lines and attend to the multiple entanglements between the artist’s political cartoons and the many lines of settler-colonialism, such as boundaries, frontiers, roads, pipelines, spatial construction, buildings, and planning.